THE ROLE OF SYARIA BUSINESS COMMUNICATION TO INCREASE CREADIBILITY AND REPUTITATON IN THE DIGITAL ERA - Muwaffaq Azzami Abidat; Rival Fauzan (Gunung Djati Conference Series, 2025)
The strategic importance of Islamic business communication in boosting a company's reputation and credibility in the digital age is examined in this article. Since information technology is developing so quickly, business players must adjust to digital platforms while maintaining Islamic principles like justice, openness, honesty (sidq), and reliability (amanah). Communication functions as a kind of da'wah and spiritual branding in addition to being a marketing tool for Sharia-compliant companies. Using a descriptive qualitative methodology and case studies of three Sharia-based organizations—Halal Corner, Elzatta Hijab, and Bank Syariah Indonesia (BSI)—this study shows that value-driven communication promotes customer loyalty and trust, which helps to establish a company's reputation over time. Digital tactics that put an emphasis on engagement, education, and adherence to Islamic principles work well for building strong emotional bonds between companies and contemporary Muslim customers. According to the findings, Islamic business communication can provide an ethical communication model in an era of digital disruption and be a significant differentiator in a competitive market. Thus, including Islamic values into communication plans is not only the right thing to do, but it also gives businesses a competitive edge in today's market.